Satisfaction Derived by the Airtel Subscribers in Coimbatore - Kumar, R. Vijay; Ruthra Priya, P. (Indian Journal of Marketing, 2006)
Mobile phones have become an essential and important device for communication in the modern days. Mobile phone communication is a part of telecommunications, which comes in the form of oral communication. Mobile devices are growing in popularity with reduction in prices and improved functionality. Consumers prefer the flexibility and versatility of mobile phone devices. Mobile phone facilitates easy and faster means of communication and one can communicate with family and friends and transact the business anywhere, anytime at a reasonable cost.